Graphite modified sodium alginate hydrogel composite for efficient removal of malachite green dye - Verma, Ankit; Thakur, Sourbh; Mamba, Gcina; Prateek; Gupta, Raju Kumar; Thakur, Pankaj; Thakur, Vijay Kumar (Elsevier, 2020)
Herein, porous sodium alginate/graphite based hybrid hydrogel was fabricated as an effective adsorbent for organic pollutant. Sodium alginate was modified through graft polymerization of acrylic acid and subsequently loaded with graphite powder to enhance its adsorption capability. The synthesized sodium alginate cross-linked acrylic acid/graphite (NaA-cl-AAc/GP) hydrogel composite was utilized in the removal of malachite green (MG) dye from aqueous solution using batch adsorption experiments. The NaA-cl-AAc/GP hydrogel composite was characterized by infrared spectroscopy, Raman spectroscopy, thermo-gravimetric analysis, scanning electron microscopy, x-ray photoelectron spectroscopy and x-ray diffraction. Under optimized experimental conditions, a maximum adsorption capacity of 628.93 mg g−1 was attained for malachite green dye. Moreover, the adsorption process could be well described by the Langmuir isotherm model and pseudo-second-order kinetic model. The hydrogel composite also showed 91% adsorption after three consecutive cycles of dye adsorption-desorption. Therefore, the NaA-cl-AAc/GP hydrogel composite is a potentially favourable material towards dye pollution remediation owing to its better swelling rate, environment friendliness, high adsorption potential and regeneration capability.
Keywords: Graphite; Sodium alginate; Malachite green; Water pollution; Dye removal